The causal effects of systemic antioxidant capacity on male infertility: A two-sample mendelian randomization analysis - Xiaolong Zhang; Zhirong Zhu; Chaodong Shen; Guiliang Tang (Scientific Reports)
Abstract The present research aimed to assess the potential causal relationship between systemic antioxidant capacity and male infertility using a two-sample Mendelian randomization approach. The primary MR analysis utilized the inverse variance weighted (IVW)method, supplemented by complementary analyses including MR-Egger, weighted mode, simple mode, and weighted median methods. For male infertility, the available summarized data were gained from the open database (IEU OPEN GWAS PROJECT), which includes a total of 680 male patients with infertility and 72,799 controls of European population.10 biomarkers related to systemic antioxidant capacity were examined to investigate their potential association with male infertility, including glutathione S-transferase (GST), superoxide dismutase(SOD), glutathione peroxidase(GPX), catalase (CAT), total bilirubin, albumin, α-tocopherol, ascorbate, retinol, and uric acid. MR analyses using IVW mode revealed that genetically determined systemic antioxidant capacity biomarkers had no causal effects on male infertility risk, including GST(OR = 1.08, 95%CI: 0.91–1.29, P = 0.35), SOD(OR = 0.83, 95%CI: 0.66–1.04, P = 0.11), GPX(OR = 1.12, 95%CI: 0.92–1.36,P = 0.26), CAT(OR = 1.04, 95%CI: 0.83–1.29, P = 0.75), total bilirubin(OR = 0.98, 95%CI: 0.94–1.01, P = 0.18), albumin(OR = 1.14, 95%CI: 0.73–1.76, P = 0.57), α-tocopherol(OR = 0.56, 95%CI: 0.03–9.38, P = 0.69), ascorbate(OR = 1.06, 95%CI: 0.24–4.60, P = 0.94), retinol(OR = 1.29, 95%CI: 0.34–4.96, P = 0.71), and uric acid (OR = 0.88, 95% CI : 0.67–1.17, P = 0.39). The current study found no significantly causal link between systemic antioxidant capacity and male infertility. Further research with larger sample sizes and data from different ethnicities is needed.